Synthesis of N-(Isoquinolin-1-yl)sulfonamides via Ag2O-catalyzed tandem reaction of ortho-alkynylbenzaldoximes with benchtop stabilized ketenimines - Hayatgheybi, Sepideh; Khosravi, Hormoz; Zahedian Tejeneki, Hossein; Rominger, Frank; Bijanzadeh, Hamid Reza; Balalaie, Saeed (Organic letters, 2021)
In this project, a moderately efficient approach to multisubstituted N-(isoquinolin-1-yl)sulfonamide derivatives was illustrated, utilizing ortho-alkynylbenzaldoximes and zwitterionic ketenimine salts in a tandem reaction catalyzed by silver oxide. The oxophilicity of Ag2O, along with its nature as Lewis acid, pave the way for a smooth [3 + 2] cycloaddition between isoquinoline N-oxides and ketenimine species, which is a key step in this reaction. DFT calculation suggests that 1,3-dipolar cycloaddition of nitrone and ketenimine proceeds through a selective stepwise mechanism.
Im Text ist "2" tiefgestellt
Gesehen am 01.03.2022